Pertumbuhan Ekonomi Pasca Pandemi Covid – 19 Serta Peran Pemerintah Dalam Pemulihan Ekonomi Di Kota Medan - Monic Cristin Simare Marea; Sondang Desmita Elpades; Anita Manihuruk; Sondang Lusiana Sinaga; Riris Serlina Sirait; Dayana Rabecca Tampubolon (CV. ITTC INDONESIA, 2026)
This study explores the strategies and effectiveness of the recovery of Micro, Small, and Medium Enterprises (MSMEs) in Medan City following the COVID-19 pandemic. By reviewing recent scholarly articles, it examines the roles of government policies, digital transformation, product diversification, and multistakeholder collaboration in supporting MSME sustainability. The review findings show that economic stimulus policies such as cash assistance, credit relaxation, and digital training significantly impact the resilience and growth of MSMEs. Moreover, MSMEs' adaptation to technology and the role of communities further strengthen local economic resilience. This study contributes to the literature on regional economic recovery and serves as a foundation for data-driven policy-making.